Numerical study on a porous material subject to SiC particles deposition, using OpenFOAM and sensitivity analysis technique: Effect of clogging evolution on the thermal performances - Akridiss Abed, S.; Settar, A.; Chetehouna, K.; Kadiri, M.S.; El Tabach, E.; Gascoin, N. (Chemical engineering science, 2020)
•Particles’ deposition effect on the thermal efficiency of porous materials.•Numerical study of the involved phenomena using a homemade solver in OpenFOAM.•Prediction of clogging states using global sensitivity analysis approach.•Heat exchange is mainly affected by solid thermal conductivity and fluid velocity.•Clogging evolution affects substantially the cooling process by transpiration. The high thermal load endured by scramjets can cause many damages to the combustion chamber walls of the engine which requires an efficient cooling of the latter. The method of transpiration cooling has shown to be an efficient technique of heat management, by sending a cold fluid through the porous walls of the combustion chamber to cool them. Various parameters could affect the hydrodynamic and thermal behaviours involved at the porous wall, such as the thermal conductivities, the material porosity, the velocity of the flow and other inputs. The present work consists of two-dimensional numerical study of the thermal behaviour of bronze-based porous medium (BR30) using an OpenFOAM house-code. The porous matrix is crossed by water as fluid cooling in laminar flow, while, constant temperatures are applied in contact of combustion chamber. The Local Thermal Non-Equilibrium (LTNE) is considered in the internal field. The developed code was validated against both experimental and numerical results from the literature. Afterwards, two clogged porous media (clogging level of 21% and 32%) are investigated from the thermal and hydrodynamic point of view. Then after, both porous mediums are compared to the nominal configuration (without clogging). The results have shown that the clogging of the material affected not only the hydrodynamic behaviour of the flow but also the thermal properties of the material. Moreover, it has been shown that the clogged materials heated quicker and more that the clean one, while the two clogged materials didn’t show a noticeable difference. To understand the effect of different parameters affecting the cooling system efficiency, a global sensitivity analysis is then conducted to determine the most important parameter by varying each one in a range of 10%. The solid thermal conductivity as well as the fluid velocity are the most influencing parameters on the temperature. The interaction of the parameters has also been studied and shown that the interactions of the fluid velocity, solid thermal conductivity as well as the porosity with other parameters have more effect on the resulting temperature.